2019
DOI: 10.1289/ehp4093
|View full text |Cite
|
Sign up to set email alerts
|

Tap Water Contributions to Plasma Concentrations of Poly- and Perfluoroalkyl Substances (PFAS) in a Nationwide Prospective Cohort of U.S. Women

Abstract: Background:Between 2013 and 2015, concentrations of poly- and perfluoroalkyl substances (PFAS) in public drinking water supplies serving at least six million individuals exceeded the level set forth in the health advisory established by the U.S. Environmental Protection Agency. Other than data reported for contaminated sites, no systematic or prospective data exist on the relative source contribution (RSC) of drinking water to human PFAS exposures.Objectives:This study estimates the RSC of tap water to overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 67 publications
1
61
1
Order By: Relevance
“…Data (ng/L) averaged from multiple sources: (Evens et al., 2020; Hu et al., 2019; Kim et al., 2019). Calculation of ng/kg bw/day = (ng/L) x (3.2L/70 kg bw/day) (Sawka, 2005).…”
Section: Pfas Propertiesmentioning
confidence: 99%
“…Data (ng/L) averaged from multiple sources: (Evens et al., 2020; Hu et al., 2019; Kim et al., 2019). Calculation of ng/kg bw/day = (ng/L) x (3.2L/70 kg bw/day) (Sawka, 2005).…”
Section: Pfas Propertiesmentioning
confidence: 99%
“…35 Finally, in a recent study on adult women from the general population in the U.S. it was observed that tap water concentrations of PFOA (<100 ng L À1 ) and peruorononanoic acid (PFNA) (median: #2 ng L À1 of single PFAA) were associated with plasma concentrations among individuals that reported drinking >8 cups of drinking water per day. 36 No associations were found for PFOS and peruorohexane sulfonic acid (PFHxS).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, consumption of PFOA and microcystins is associated with very serious health problems such as elevated blood cholesterol, gastrointestinal infection, depressed immune system, kidney and liver disease, diabetes, and cancer. Also, growth deficiency among little children has been reported [2][3][4][5][6][7][8][9]. e US EPA health regulatory limit for PFOA in drinking water is < 0.07 μg/L and the WHO guidelines limit for microcystins lifetime exposure is 1.0 μg/L [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, its thermal stability, surfactant behavior, and stainresistant properties are the reason for its wide use in the production of industrial items like fluoropolymer products, firefighting foams, stain-resistant coatings, and electroplating [15]. PFOA is not lipophilic, which means that it can bind to serum albumin making it hard to excrete from the human body [4][5][6][7]16]. On the other hand, microcystins belong to a family of stable monocyclic heptapeptide compounds, of which nearly 80 variants are now known.…”
Section: Introductionmentioning
confidence: 99%